Working Conditions Influencing Junior School Principalship as a Satisfying Profession: A Cross-Country Comparative Study - Ning, Bo; Liu, Hongqiang; Cui, Yiming (Frontiers in Psychology, 2022)
Although prior studies have extensively investigated the effect of working conditions upon professional satisfaction, the cross-national variance in the effect remains largely understudied due to technical or financial restrictions. The Teaching and Learning International Survey (TALIS) provides an opportunity to investigate the cross-country differences in the impact of working conditions upon principals’ professional satisfaction. The current study attempts to investigate the overall and specific effects of principals’ workplace environment satisfaction, rewards satisfaction, and workload stress on their professional satisfaction in 47 countries included in the TALIS 2018. The results indicate that workplace environment, rather than the typically regarded effort-reward issues, is the most powerful contributor to individual principals’ professional satisfaction across 47 countries, while, in countries with low overall professional satisfaction, rewards satisfaction and workload stress are more powerful predictors for principals’ professional satisfaction on the country level. This study may inform policymakers in school principal stimulation and retention that effective practice to stimulate and/or retain school principals may vary across countries and research findings derived from data on the individual level may not be applicable to practice on the country level.